The Spectre of Race : How Discrimination Haunts Western Democracy - Hanchard, Michael George (Princeton, New Jersey : Princeton University Press : Princeton University Press, 2018)
How racism and discrimination have been central to democracies from the classical period to todayAs right-wing nationalism and authoritarian populism gain momentum across the world, liberals, and even some conservatives, worry that democratic principles are under threat. In The Spectre of Race, Michael Hanchard argues that the current rise in xenophobia and racist rhetoric is nothing new and that exclusionary policies have always been central to democratic practices since their beginnings in classical times. Contending that democracy has never been for all people, Hanchard discusses how marginalization is reinforced in modern politics, and why these contradictions need to be fully examined if the dynamics of democracy are to be truly understood. Hanchard identifies continuities of discriminatory citizenship from classical Athens to the present and looks at how democratic institutions have promoted undemocratic ideas and practices. The longest-standing modern democracies--France, Britain, and the United States--profited from slave labor, empire, and colonialism, much like their Athenian predecessor. Hanchard follows these patterns through the Enlightenment and to the states and political thinkers of the late nineteenth and early twentieth centuries, and he examines how early political scientists, including Woodrow Wilson and his contemporaries, devised what Hanchard has characterized as "racial regimes" to maintain the political and economic privileges of dominant groups at the expense of subordinated ones. Exploring how democracies reconcile political inequality and equality, Hanchard debates the thorny question of the conditions under which democracies have created and maintained barriers to political membership. Showing the ways that race, gender, nationality, and other criteria have determined a person's status in political life, The Spectre ofRace offers important historical context for how democracy generates political difference and inequality.
Cover; Title; Copyright; Dedication; CONTENTS; Acknowledgements; Introduction: How Discrimination Haunts Western Democracy; 1 Edward Augustus Freeman and the Dawn of Comparative Politics; 2 Race Development, Political Development; 3 Society and Polity, Difference and Inequality; 4 Racial and Ethno-National Regimes in Liberal Polities; 5 Conclusion: Reconfiguring Comparative Politics and Democracy; Postscript: From Athens to Charlottesville; Appendix; Notes; Bibliography; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 30, 2018).
In English.
JSTOR
Keywords: Race discrimination; Political theology and race; Discrimination raciale; Théologie politique et race; racial discrimination; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; POLITICAL SCIENCE -- Civics & Citizenship; Political theology and race; Race discrimination; Aristotle; Aryan; Charles Merriam; Edward Augustus Freeman; Edward Vogelin; Euro-Aryan.; Gabriel Almond; George Fredrickson; Hannah Arendt; Herbert Baxter Adams; Italian; Nazism; Samuel Huntington; Sidney Verba; Teutonic; Western democratic tradition; World War II; autochthony; citizen; comparative politics; difference and polity; endogenous; ethno-national.; ethnos; exogenous; nation state; political equality; political subjects; politics of developing areas; polyarchy; property; racial characteristics; racism; self-governance.; slavery; social inequality; sovereign state; History